Potassium nitrate priming to mitigate the salt stress on cucumber seedlings - Oliveira, Carlos Eduardo da Silva; Steiner, Fábio (Scientia Agraria Paranaensis, 2017)
Salinity is one of the abiotic stresses that further limit the seed germination and growth of plants because of low water potential of the soil. In this study, seeds of cucumber (Cucumis sativus L., cv. Aodai Melhorado) were used to investigate the effects of potassium nitrate priming on germination and early seedling growth under different salinity levels. It was hypothesized that priming with potassium nitrate may improve seed germination and plant establishment by mitigating the negative effects of saline stress through its role in cell osmotic balance. The seeds were soaked in distilled water or in a 2 g L-1 KNO3 solution at 25 ºC for 6 hours, and after drying, were distributed in plastic boxes with blotter paper containing different salt solutions prepared with concentrations of 0 (control), 25, 50, 75 and 100 mmol NaCl L-1. The plastic boxes were kept into a seed germinator, at 25 ºC for 10 days. A completely randomized design in a 2 x 5 factorial scheme with four replications of 25 seeds each was used. The results showed that the priming of cucumber seeds with potassium nitrate had little effect to improve germination capacity and growth rate of seedlings under salt stress conditions. Low salt concentrations may induce osmotic adjustment activity in the cucumber plants and lead to increases in hypocotyl and radicle length of seedlings, whereas higher concentrations cause severe inhibition of plant growth. The “Aodai Melhorado” cucumber cultivar is a moderately tolerant genotype to salt stress during the germination and seedling establishment stage by presenting yield stability index greater than 0.50 until the level of 100 mmol NaCl L-1.